Enumeration of Coliform Bacteria and E. coli Contaminating the Drinking Water of Al Gedarif City - Abdel Daim, Zeinab J.; Abdel-Rahim, Awad M.; Ahmed, Abdulwahab Ali (Gezira Journal of Engineering and Applied Sciences, 2018)
ABSTRACT The present study enumerated the bacteriological contamination of   the main sources of drinking water in Al Gedarif city. A total of 134 water samples (raw waters, treated waters, main reservoirs, main pipelines, and sabeel zeer waters) were tested for their total coliforms and E. coli counts, using the most probable number technique (MPN). The results indicated that the total coliform and E. coli counts were lower in the ground water sources (Al Azaza and Abu Al Naja boreholes) than that in the surface sources (Atbara River, Al Saraf and Dalassa dams). Moreover, both counts in most of the zeer water samples were higher than those of the other sources. It was also noticed that the zeers located in public areas (market) were more contaminated than the other sabeel zeers. The seasonal variations study was performed for the surface sources, where it was found that the maximum densities of coliform bacteria and    E. coli were occurred during the autumn season and the summer, while the periodical variations study was made for the ground sources, where the coliforms and E. coli densities were found almost higher during the second period of each year.